A Pilot Randomized Controlled Trial to Assess the Impact of Motivational Interviewing on Initiating Behavioral Therapy for Migraine. Issue 2 (24th January 2020) - Minen, Mia T.; Sahyoun, Gabriella; Gopal, Ariana; Levitan, Valeriya; Pirraglia, Elizabeth; Simon, Naomi M.; Halpern, Audrey
Abstract : Background: Relaxation, biofeedback, and cognitive behavioral therapy are evidence‐based behavioral therapies for migraine. Despite such efficacy, research shows that only about half of patients initiate behavioral therapy recommended by their headache specialists. Objective: Motivational interviewing (MI) is a widely used method to help patients explore and overcome ambivalence to enact positive life changes. We tested the hypothesis that telephone‐based MI would improve initiation, scheduling, and attending behavioral therapy for migraine. Methods: Single‐blind randomized controlled trial comparing telephone‐based MI to treatment as usual (TAU). Participants were recruited during their appointments with headache specialists at two sites of a New York City medical center. Inclusion criteria: ages from 16 to 80, migraine diagnosis by United Council of Neurologic Subspecialty fellowship trained and/or certified headache specialist, and referral for behavioral therapy for prevention in the appointment of recruitment. Exclusion criteria: having done behavioral therapy for migraine in the past year. Participants in the MI group received up to 5 MI calls. TAU participants were called after 3 months for general follow‐up data. The prespecified primary outcome was scheduling a behavioral therapy appointment, and secondary outcomes were initiating and attending a behavioral therapy appointment. Results: 76 patients were enrolled and randomized (MI = 36, TAU = 40). At baseline, the mean number of headache days was 12.0 ± 9.0. Self‐reported anxiety was present for 36/52 (69.2%) and depression for 30/52 (57.7%). Follow‐up assessments were completed for 77.6% (59/76, MI = 32, TAU = 27). The mean number of MI calls per participant was 2.69 ± 1.56 [0 to 5]. There was a greater likelihood of those in the MI group to initiating an appointment (22/32, 68.8% vs 11/27, 40.7%, P = .0309). There were no differences in appointment scheduling or attendance. Reasons stated for not initiating behavioral therapy were lack of time, lack of insurance/funding, prioritizing other treatments, and travel plans. Conclusions: Brief telephone‐based MI may improve rates of initiation of behavioral therapy for migraine, but other barriers appear to lessen the impact on scheduling and attending behavioral therapy appointments.